ABSCISIC ACID ACCUMULATION AND PHYSIOLOGICAL INDICES IN RESPONSES TO DROUGHT STRESS IN WHEAT GENOTYPES - & et al., Qadir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study to determine how tolerant wheat genotypes to drought stress. Three drought tolerant Triticum aestivum L. genotypes; Rizgary, Sham-6 and Abu-Ghraib compared with three drought-susceptible; IPA95, Tammuz-2 and IPA99 under water deficit 20% WHC (Water Holding Capacity). ABA level, drought related parameters; shoot and root dry weights, root and shoot ratio. As well as Leaf relative water content (LRWC %), membrane stability index (MSI %) and proline content determined in the leaves. A considerable increase of ABA noted in drought tolerant as compared to susceptible genotypes under drought stress condition. That is led to reduction in shoot dry weight in Rizgary, Sham-6 and Abu-ghreb; 2.71, 2.70 and 2.62 g/plant respectively. In addition they adapted to proliferate larger root system with 2.63, 2.16 and 1.71 g/plant respectively. Consequently the ratio of root: shoot increased; 0.98, 0.80 and 0.66. Rizgary, Sham-6 and Abu-ghreb retained a significantly higher LRWCs %; 79.81, 77.17 and 78.53 % respectively at 20 % WHC as compared to susceptible genotypes. Membrane Stability Index (MSI %) decreased significantly at lower rate in tolerant genotypes; 65.69, 67.28 and 67.18 % respectively. As well as proline increased as an osmoticum to reduce the harmful effect of drought on plant cell in resistant genotypes; Rizgary, Sham-6 and Abu-ghreb; 0.71, 0.72 and 0.61 mg g-1 D. in sequence as compared to sensitive genotypes. The tolerant genotypes have stronger adaptability mechanisms to cope water scarcity as compared to susceptible genotypes.